A pair of mononuclear Dy(iii) enantiomers showing single-ion magnetic and ferroelectric properties. (1st June 2018) - Li, Xi-Li; Zhu, Cancan; Rong, Qixiang; Wei, Jiahao; Li, Ruixue; Liu, Cai-Ming
Abstract : A new pair of Dy(iii )-β-diketonate enantiomers with chiral N, N ′-donor ligands display chiroptical activities and ferroelectric and single-ion magnetic properties, and act as potential multifunctional molecule-based materials. Abstract : Using enantiopure ligands (–)/(+)-4, 5-pinene-2, 2′-bipyridine (L R /L S ) to react with Dy(btfa)3 ·2H2 O, respectively, a pair of Dy(iii ) enantiomers with the formulae Dy(btfa)3 L R ( R -1 ) and Dy(btfa)3 L S ( S -1, btfa − = 3-benzoly-1, 1, 1-trifluoroacetonate) were obtained and structurally characterized. Each Dy(iii ) ion in R -1 and S -1 is octa-coordinate and adopts approximately a square-antiprismatic (SAP) geometry with D 4d symmetry. Studies on the magnetic and ferroelectric properties of R -1 were carried out and the investigation results of the magnetic properties revealed that it displays a slow magnetic relaxation behavior under a zero direct-current (dc) field, confirming its single-ion magnetic (SIM) characteristic with an effective energy barrier of 95.4(1.5) K. Moreover, R -1 crystallizes in the ferroelectric point group C 1, and exhibits ferroelectricity with a notable remnant polarization ( P r ) value of 3.75 μC cm −2 at room temperature. All these research results also suggested that R -1 and S -1 are potential multifunctional molecule-based materials combining chiroptical activities, and ferroelectric and SIM properties within one molecule.